Chenier Morphodynamics on the Amazon-Influenced Coast of Suriname, South America: Implications for Beach Ecosystem Services - Anthony, Edward J.; Brunier, Guillaume; Gardel, Antoine; Hiwat, Michael (Frontiers in Earth Science, 2019)
The 350-km long coast of Suriname, South America, is part of a unique system in the world characterized by large-scale mud supply from the Amazon and exposed to Atlantic waves. Large banks migrate alongshore from the Amazon to the Orinoco delta, separated by ‘inter-bank’ zones. Banks dissipate waves, partially weld onshore, and are colonized by mangroves, whereas waves in inter-bank areas cause shoreline erosion, mitigated where rare cheniers develop. Cheniers assure coastal protection and recreational and ecosystem services, notably providing nesting sites for marine turtles. Cheniers are also under pressure from sand mining. In order to gain a better understanding of how these cheniers form and evolve, a study was conducted on Braamspunt beach, a major turtle-nesting chenier in Suriname constructed from sand supplied by the Maroni River. Satellite images between 1987 and 2018 show a reduction of the alongshore extent of the chenier, following sand supply cut-off from the Maroni by a mud bank migrating westward towards the mouth of the Suriname River, exacerbated by mud-blanketing of sand. Commercial sand mining has further affected the beach, but mined volumes are not known. Field surveys (high-resolution topography, drone photogrammetry, wave measurements) conducted in February, 2016 highlight two chenier types depending on sand availability, transport and wave reworking: a high-tide reflective/low-tide dissipative and longshore transport-dominated type 1 exhibiting berm scarping, and a low, overwash-dominated type 2. As the mud-bank’s leading edge impinges on the inter-bank trailing edge, sand sequestering by mud and storage in type 2 washovers entail less available sand downdrift. Type 1 lost over 4200 m3 of sand in just 3–4 days. An increasingly deficient budget induces progressive change to type 2, morphodynamically better adapted to diminution of available sand, and epitomizing chenier fragmentation and isolation within the muddy Guianas coastal plain. By affecting the morphology and sand budget of Braamspunt, these changes lower opportunities for turtle-nesting. Further reduction of the length of exposed chenier is apparently halted near the Suriname River mouth where mud is liquefied by the outflowing river and tidal jet, but the continued existence of this preserved beach could be endangered by sand mining.